Some undesirable traps which can mislead the pathologist. Issue 9 (30th April 2021) - Mercier, Victor; Sasso, Milène; Kouyoumdjian, Pascal; Sizaret, Damien; Benzimra, Simon; Gonzalez, Samia; Desoubeaux, Guillaume
Abstract : In clinical laboratories, the diagnosis of parasite diseases can sometimes be challenging for non-expert microbiologists. Indeed, in spite of the advent of the molecular biology, macroscopic and microscopic examinations still remain essential. Nonetheless, it is usually not automated and requires great skills to complete the correct diagnosis. It is not infrequent that inert elements mislead to erroneous diagnoses. Through three different concrete examples, this article aims at underscoring the actual risk of parasite misidentification and at highlighting the systematic approach to be conducted in order to enable reliable diagnosis.